Pregnant women's decision-making capacity and adherence to iron supplementation in sub-Saharan Africa: a multi-country analysis of 25 countries - Betregiorgis Zegeye; Nicholas Kofi Adjei; Comfort Z. Olorunsaiye; Bright Opoku Ahinkorah; Edward Kwabena Ameyaw; Abdul-Aziz Seidu; Sanni Yaya (BMC, 2021)
Abstract Background Anaemia and related complications during pregnancy is a global problem but more prevalent in sub-Sahara Africa (SSA). Women's decision-making power has significantly been linked with maternal health service utilization but there is inadequate evidence about adherence to iron supplementation. This study therefore assessed the association between household decision-making power and iron supplementation adherence among pregnant married women in 25 sub-Saharan African countries. Methods We used data from the Demographic and Health Surveys (DHS) of 25 sub-Saharan African countries conducted between 2010 and 2019. Women's decision-making power was measured by three parameters; own health care, making large household purchases and visits to her family or relatives. The association between women's decision-making power and iron supplementation adherence was assessed using logistic regressions, adjusting for confounders. The results were presented as adjusted odds ratio (AOR) with 95% confidence intervals (CIs). Results Approximately 65.4% of pregnant married women had made decisions either alone or with husband in all three decisions making parameters (i.e., own health care, making large household purchases, visits to her family or relatives). The rate of adherence to iron medication during pregnancy was 51.7% (95% CI; 48.5-54.9%). Adherence to iron supplementation was found to be higher among pregnant married women who had decision-making power (AOR = 1.46, 95% CI; 1.16-1.83), secondary education (AOR = 1.45, 95% CI; 1.05-2.00) and antenatal care visit (AOR = 2.77, 95% CI; 2.19-3.51). Wealth quintiles and religion were significantly associated with adherence to iron supplementation. Conclusions Adherence to iron supplementation is high among pregnant women in SSA. Decision making power, educational status and antenatal care visit were found to be significantly associated with adherence to these supplements. These findings highlight that there is a need to design interventions that enhance women's decision-making capacities, and empowering them through education to improve the coverage of antenatal iron supplementation.